Adipose tissue fatty acid metabolism and cardiovascular disease. - Frayn, K; Fielding, B; Karpe, F (2005)
PURPOSE OF REVIEW: Fatty acid and triacylglycerol metabolism in adipose tissue may be involved in the generation of risk factors for cardiovascular disease and type 2 diabetes. Pharmaceutical companies are targeting adipocyte metabolism in their search for drugs for treating, or reducing the risk of, these conditions. We review new developments in adipose tissue fatty acid metabolism and how that might relate to cardiovascular disease. RECENT FINDINGS: Fatty acid release from human adipose tissue is oscillatory, with a period of about 12 min. Remarkably, oscillatory fatty acid release is also seen in isolated adipocytes. Further evidence has emerged that not all adipose depots are equal, and that lower-body adipose tissue may exert protective effects against cardiovascular disease. There have been a number of developments in the area of fatty acid handling by adipocytes. Fatty acid binding proteins are clearly important in regulating fatty acid metabolism, with striking protection against atherosclerosis in mice deficient in both the binding proteins expressed in adipocytes. The demonstration that adipocytes lacking hormone-sensitive lipase still display lipolysis has led to the identification of novel lipases that may play crucial roles in adipose tissue fatty acid metabolism. Further evidence has accrued of the interaction between hormone-sensitive lipase and perilipin, the protein that coats the adipocyte lipid droplet. SUMMARY: Recent developments in our understanding of adipose tissue fatty acid metabolism open up the possibility of new pharmaceutical targets. However, interference with adipose tissue fatty acid metabolism is not to be undertaken lightly and needs a clear understanding of the normal role of adipocyte lipolysis.